The Effect Of Work Discipline And Work Motivation On Work Productivity At The Lahat Regency Fire And Rescue Service - Supriono Supriono; Tri Rusilawati; Amaludin Amaludin (Journal of Management, Economic, and Accounting, 2026)
This study is entitled "The Influence of Work Discipline and Work Motivation on Employee Productivity at the Lahat Regency Fire and Rescue Service." This study aims to determine the influence of Work Discipline on Work Productivity and the influence of Work Motivation on Work Productivity at the Lahat Regency Fire and Rescue Service Kabupaten Lahat. The number of respondents in this study was 41 employees, the analysis method used was qualitative and quantitative descriptive analysis, namely by comparing existing theories and realities, by collecting data through questionnaires on 41 respondents, the questionnaires made were related to 3 (three) variables, namely Work Discipline, Work Motivation and Work Productivity, Data processing or data calculations using SPSS Statistic versi 30. Based on the results of the Multiple Linear Regression test b1 (regression coefficient value X1) has a positive value (+) of 0.032, it can be interpreted that if variable X1 increases, variable Y will also increase and vice versa, b2 (regression coefficient value X2) has a negative value (-) of - 0.009, it can be interpreted that if variable X2 increases, variable Y will decrease, and vice versa, The results of the t test (partial) show that the significance value of the influence of Work Discipline (X1) on Work Productivity (Y) is 0.001 < 0.05 and the calculated t value is 6.615 > the t table value of 1.685, so Ho is rejected and Ha is accepted, meaning that there is a significant influence of Work Discipline (X1) on Work Productivity (Y), the t test (partial) shows that the significance value of the influence of Work Motivation (X2) on Work Productivity (Y) is 0.001 < 0.05 and the calculated t value is 6.786 > The t table value is 1.685, so Ho is rejected and Ha is accepted, meaning that there is a significant influence of Work Motivation (X1) on Work Productivity (Y). The F test (Simultaneous Test) shows that the significant value for Variable X1 and Variable X2 on Variable Y is 0.960 > 0.05 and F count is 0.041 < F table value of 3.24. This proves that Ho is accepted and Ha is rejected, meaning that there is no significant influence of Variable X1 and Variable X2 on Variable Y.